2010
DOI: 10.1111/j.1540-8167.2010.01742.x
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected High Incidence of Esophageal Injury Following Pulmonary Vein Isolation Using Robotic Navigation

Abstract: A high incidence of thermal esophageal injury including a perforation was noted following robotic PVI using 30 W along the posterior LA wall. During RN-based PVI procedures esophageal temperature monitoring is advocated. Reduction of ablation power to 20 W and termination of energy delivery at T(eso) of 41 degrees C significantly reduced the risk of esophageal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
49
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 25 publications
4
49
1
2
Order By: Relevance
“…Some of the well-identified UGI system complications, including atrioesophageal fistulae, esophageal ulcerations, gastroesophageal reflux, acute pyloric spasm, and gastric hypomotility, are at least partially a consequence of VN injury. [3][4][5][6][7][8][9][10][11] Because the consequences of UGI injury can be catastrophic, the importance of understanding the effect of AF ablation on VN injury cannot be overstated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the well-identified UGI system complications, including atrioesophageal fistulae, esophageal ulcerations, gastroesophageal reflux, acute pyloric spasm, and gastric hypomotility, are at least partially a consequence of VN injury. [3][4][5][6][7][8][9][10][11] Because the consequences of UGI injury can be catastrophic, the importance of understanding the effect of AF ablation on VN injury cannot be overstated.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the reported UGI complications resulting from AF ablation include atrioesophageal fistulae, esophageal mucosal ulcerations with or without bleeding, gastroesophageal reflux, pyloric spasm, and gastric hypomotility. [3][4][5][6][7][8][9][10][11] The exact mechanism of these injuries is not known; however, injury to the vagus nerve (VN) and its components are proposed to be one of the major players in many of these complications. 5,10 The VN because of its close proximity to the posterior wall of the LA is susceptible to the thermal injury from RFA.…”
mentioning
confidence: 99%
“…Theoretically, measurement of contact force should also prevent excessively high force and wall perforation. One previous study found a relatively high incidence of esophageal lesions after robotic AF ablation 16 . Even though a different robotic system was used and no contact force was measured the results of the study by Tilz et al may at least in part apply to the RCS used in our protocol.…”
Section: Discussionmentioning
confidence: 99%
“…65,66 While insufficient contact force may result in an ineffective lesion, excessive contact force may result in complications such as heart wall perforation, steam pops, thrombus formation or oesophageal injury. 54,67,68 From the foregoing we can safely propose that catheter contact sensors might allow the creation of more uniform ablation lesions and increase the safety of RF delivery. Less experienced electrophysiologists might ensure less variability in manipulations and avoid excessive contact force.…”
Section: Radiofrequency-based Pulmonary Vein Isolation By Contact Monmentioning
confidence: 99%
“…The use of power limit to 20 W along the posterior wall in combination with an oesophageal temperature limit of 41 degrees Celsius significantly reduced the risk of oesophageal injury. 54 Considering that remote navigation may provide higher stability and subsequent more predictable RF lesions, 55 it seems reasonable to limit application time at a single spot to 20 seconds, concomitantly to set up maximum power at 30 W and decrease it to 15-20 W when ablating on the posterior wall.…”
Section: Pulmonary Vein Isolation By Remote Navigationmentioning
confidence: 99%